Penerapan Komunikasi Total Dalam Meningkatkan Kualitas Ineraksi Sosial Bagi Anak Tunarungu di SD Gmim 140 Pineleng - Zega, Anna; Marentek, L. K. M.; Mangar, Julita Kasandra (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to apply total communication to improve language skills and help deaf children improve their ability to use spoken language, sign language, writing, or a combination of all of these communications. By improving communication skills, deaf children can interact more effectively with others in various social contexts. In this research, a single subject research approach or SSR (Single Subject Research) is used because only one subject will be studied. The data collection procedure in this research is by observing and interviewing selected information as well as documents related to the issues raised. The results of this research based on data analysis can be proven that the effect of intervention using total communication policies can improve the quality of social interactions for deaf children at SD GMIM 140 Pineleng